Superior Ophthalmic Vein Thrombosis with Cerebral Venous Sinus Thrombosis: A Rare Entity in a Child (Journal of Enam Medical College, 2019)
Cerebral venous sinus thrombosis (CVST) is a rare stroke-like syndrome. Sometimes it may be rarely associated with ophthalmic vein occlusion. We present a 10-year-old girl who had severe headache, diplopia, severe congestion of eye, proptosis and orbital pain. She had no signs of meninigeal irritation, no focal deficit except left sided lateral rectus palsy and altered visual acuity. Investigations regarding vasculitis and thrombophillia were normal except thrombocytosis. MRI of brain showed ‘dense triangle sign’ and thickened superior ophthalmic vein. Magnetic resonance venography (MRV) showed occlusion of superior sagital sinus and transverse sinus. She was treated with paracetamol, acetazolamide, rivaroxaban and antibiotics followed by high dose pulse methyl prednisolone. She made a partial recovery within one week and at 3 months follow-up she was completely normal.J Enam Med Col 2019; 9(2): 127-132